2007
DOI: 10.1175/2007jtecha989.1
|View full text |Cite
|
Sign up to set email alerts
|

Development of the HIRS Outgoing Longwave Radiation Climate Dataset

Abstract: The Advanced Very High Resolution Radiometer (AVHRR) outgoing longwave radiation (OLR) product, which NOAA has been operationally generating since 1979, is a very long data record that has been used in many applications, yet past studies have shown its limitations and several algorithm-related deficiencies. Ellingson et al. have developed the multispectral algorithm that largely improved the accuracy of the narrowband-estimated OLR as well as eliminated the problems in AVHRR. NOAA has been generating High Reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
85
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(90 citation statements)
references
References 15 publications
5
85
0
Order By: Relevance
“…The analyses are for boreal summer (June-August) during the period 1979-2015. We also repeated the main analyses using the daily mean OLR Climate Data Record (CDR; available at http://olr.umd.edu/; Lee et al 2004Lee et al , 2007 and obtained similar results (not shown).…”
Section: Methodsmentioning
confidence: 62%
“…The analyses are for boreal summer (June-August) during the period 1979-2015. We also repeated the main analyses using the daily mean OLR Climate Data Record (CDR; available at http://olr.umd.edu/; Lee et al 2004Lee et al , 2007 and obtained similar results (not shown).…”
Section: Methodsmentioning
confidence: 62%
“…Vigorous validation efforts were performed for the HIRS OLR estimation technique against broadband observations derived from the Earth Radiation Budget Experiment (ERBE) and the Clouds and the Earth's Radiant Energy System (CERES) [12,13]. Details of the HIRS sensor can be found in the NOAA Polar Orbiter Data (POD) User's Guide [14], the NOAA KLM User's Guide [15], and the C-ATBD for the HIRS OLR climate data record (CDR) [16].…”
Section: Methodsmentioning
confidence: 99%
“…The HIRS OLR algorithm has been implemented to generate the NESDIS operational HIRS OLR product since September 1998, and the OLR products retrieved from operational geostationary satellites are implemented as part of the operational GOES Remote Sens. 2018, 10, 1325 3 of 13 Surface and Insolation Product (GSIP) [19]. A variant of this method has been developed for the GOES-R Advanced Baseline Imager instrument [20].…”
Section: Methodsmentioning
confidence: 99%
“…The NOAA-14 satellite, which was long lived and had a large orbital drift during its period of operation (Lee et al 2007), is used as an example. Because NOAA-14, in common with all the HIRS satellites, is in a sun-synchronous orbit, it measures each latitude at two local times per day, once in the ascending orbit mode and once in the descending.…”
Section: Diurnal Temperature Biasesmentioning
confidence: 99%